2012
DOI: 10.2147/ott.s39429
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy-verified occult subependymal dissemination of glioblastoma and brain metastasis undetected by MRI: prognostic significance

Abstract: Although various prognostic indices exist for patients with malignant brain tumors, the prognostic significance of the subependymal spread of intracranial tumors is still a matter of debate. In this paper, we report the cases of two intraventricular lesions, a recurrent glioblastoma multiforme (GBM) and a brain metastasis, each successfully treated with a neuroendoscopic approach. Thanks to this minimally invasive approach, we achieved good therapeutic results: we obtained a histological diagnosis; we controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…For example, widespread dissemination of tumor cells through CSF or along the length of VSVZ has been hypothesized [19, 32, 33]. Indeed, we noted contrast enhancement of the ipsilateral ventricular ependymal surface in a subset VSVZ+ GBMs (Supplemental Figure S3b–d).…”
Section: Discussionmentioning
confidence: 51%
“…For example, widespread dissemination of tumor cells through CSF or along the length of VSVZ has been hypothesized [19, 32, 33]. Indeed, we noted contrast enhancement of the ipsilateral ventricular ependymal surface in a subset VSVZ+ GBMs (Supplemental Figure S3b–d).…”
Section: Discussionmentioning
confidence: 51%
“…Some studies indicated that the clinician can capture subtle changes, such as integrity damage and diffusivity changes caused by peritumoral edema or tumor infiltration, in neuronal structures and fibers through multimodality MRI [ 29 33 ]. Other studies suggested that multimodality MRI can be used to distinguish high-grade gliomas from metastatic tumors [ 34 – 37 ]. Recent studies have shown that multimodality MRI is a valuable noninvasive tool in differentiating residual/recurrent gliomas from postirradiation cerebral lesion [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the endoscope may allow a clearer distinction of the interface between the tumor and the surrounding eloquent structures. [6][7][8][9][10][11][12][13][14][15][16][17] In 2008 Gore et al reported the first application of a pure endoscopic supracerebellar infratentorial approach for dealing with a pineal cyst, a minimally invasive alternative to conventional microsurgical procedures that requires no exposure of the venous sinuses. 1,18,19 However, potential bleeding coming from bridging veins and/or highly vascularized lesions may be extremely hard to control with the endoscopic instrumentation.…”
Section: Discussionmentioning
confidence: 99%